Molecular signatures of alveolar type II cell differentiation in acute respiratory distress syndrome - Zhang, Yu; Wang, Yazhe; Wen, Chunsheng; Wang, Haixu; Wang, Liping (Frontiers in Medicine, 2025)
BackgroundAcute respiratory distress syndrome (ARDS) is a life-threatening lung condition with high morbidity and mortality.MethodsWe analyzed publicly available single-cell transcriptomic and microarray datasets from murine ARDS models to characterize AT2 cell differentiation trajectories following lipopolysaccharide (LPS)-induced injury. Computational mapping of cell “trajectories” revealed distinct gene expression signatures associated with divergent repair outcomes. These findings were validated in bronchoalveolar lavage fluid (BALF) samples from ARDS patients and in an LPS-induced AT2-fibroblast co-culture model. Gene expression changes were examined at both the RNA and protein levels, and pathway enrichment analysis was used to explore underlying mechanisms.ResultsTrajectory analysis revealed two major differentiation branches of AT2 cells: one enriched for fibrotic programs (Igfbp6, Gstm1, Mgp, and Lgals1) and the other linked to epithelial repair (Tgm2, Anxa1, Ankrd1, and F3). Both branches exhibited distinct gene expression patterns in patient BALF, which was consistent with scRNA-seq findings. Functional enrichment highlighted the Wnt signaling pathway as a key regulator in the injury group, which was validated at protein levels in vitro. The co-culture models showed that prolonged LPS exposure induced AT2 cell apoptosis, fibroblast activation, and extracellular matrix protein upregulation.ConclusionThis study highlights the important role of AT2 cell differentiation in shaping disease progression in ARDS and identifies potential molecular markers and signaling pathways involved in divergent repair outcomes. Our findings provide new insight into AT2 cell-driven lung repair and potential therapeutic targets.